Predicting Flood Vulnerable Areas by Using Satellite Remote Sensing Images in Kumamoto City - Japan - Rimba, A. Besse; Miura, Fusanori (Graduate Study of Environmental Sciences, Postgraduate Program of Udayana University)
Flood is a natural disaster that occurs almost every year in Japan. Based on the flood record, it occurs during the rainy season around July each year. The aim of this research is to predict areas vulnerable to flood. The current research location is the Shiragawa watershed. This study was carried out using DEMs data, ALOS AVNIR-2 and Amedas data to produce watershed area, vegetation index, land cover map and isohyet map. DEM data with spatial resolution of 10 meters was derived from the Geospatial Information Authority of Japan (GSI) in order to show the watershed. The AVNIR-2 imagery was used to create the land cover map and the vegetation index. The land cover map was created by unsupervised method then verified by using land cover map of the Geospatial Information Authority of Japan (GSI). Vegetation index was created by using Normalize Vegetation Index (NDVI) algorithm. The isohyet was obtained using data from rain gauges stationed in Kumamoto Prefecture then interpolating by applying the kriging method. All spatial data was overlaid to create the flood vulnerability map by using Geographic Information System (GIS). This study combines all the data to predict vulnerable areas of flood. The result indicates that the flood occurs in the middle part of Shiragawa watershed.